Comparing profiles and antioxidant properties of soluble and insoluble phenolics in Perilla frutescens seed flour extracts obtained by different extraction/hydrolysis methods. (12th July 2017) - Yan, Linlin; Zheng, Guangyao
Summary: Cold‐pressed Perilla frutescens seed flour (CP‐PFSF) is a potential source of natural antioxidants. In this study, different methods were used to extract both soluble and insoluble phenolics from CP‐PFSF. Also, the phenolic profiles and antioxidant properties were compared. Results showed that soluble phenolics could be extracted using aqueous‐organic solvents, where 80% acetone resulted in the highest extraction yield and antioxidant activities. Insoluble phenolics remaining in residues could be released by acid or alkaline hydrolysis, where acid hydrolysis provided higher yield and antioxidant activities than alkaline. Soluble and insoluble phenolics could be extracted simultaneously through acid/alkaline hydrolysis, resulting in nearly the same yields for total phenolics. However, the phenolic components and antioxidant activities of extracts varied significantly, depending on the methods. Principal component analysis and correlation analysis revealed that a strategy of 80% acetone with successive acid hydrolysis steps released more rosmarinic acid, which have high antioxidant activities. Abstract : Soluble and insoluble phenolics in cold press Perilla frutescens seed flour (CP‐PFSF) were extracted by different extraction/hydrolysis methods, and their compositions and contents were analyzed by HPLC and PCA.